2014
DOI: 10.1016/j.jvs.2014.01.040
|View full text |Cite
|
Sign up to set email alerts
|

Options for treatment of spontaneous mesenteric artery dissection

Abstract: Intensive surveillance is indicated during medical therapy, and invasive intervention may be necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
107
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(114 citation statements)
references
References 114 publications
4
107
1
2
Order By: Relevance
“…In general, recent first-line therapy has been conservative management, with or without antithrombotic treatment with antiplatelet and anticoagulant therapy to prevent TL occlusion by stabilizing the intimal flap (Figure, Table). [3][4][5][6][7][8][9][10][11] For a subset of patients with persistent symptoms because of critical bowel ischemia or infarction caused by compression of the TL of the SMA or rupture of the dissecting SMA, endovascular treatment (EVT) with stents or open surgical repair (OSR) is indicated without delay. 11 In the current shift towards EVT for aortic or peripheral arterial lesions, 12 EVT predominates.…”
Section: Ogino Hmentioning
confidence: 99%
“…In general, recent first-line therapy has been conservative management, with or without antithrombotic treatment with antiplatelet and anticoagulant therapy to prevent TL occlusion by stabilizing the intimal flap (Figure, Table). [3][4][5][6][7][8][9][10][11] For a subset of patients with persistent symptoms because of critical bowel ischemia or infarction caused by compression of the TL of the SMA or rupture of the dissecting SMA, endovascular treatment (EVT) with stents or open surgical repair (OSR) is indicated without delay. 11 In the current shift towards EVT for aortic or peripheral arterial lesions, 12 EVT predominates.…”
Section: Ogino Hmentioning
confidence: 99%
“…According to the modified Sakamoto's classification, there were two cases of type II and 10 cases in type III, respectively, and all patients should be underwent conservative treatment [6]. Covered stent placement can be considered to patients who failed conservative treatment.…”
mentioning
confidence: 99%
“…The controversial discussion concerning whether asymptomatic patients should be treated to prevent a potential intestinal infarction remains unresolved [28,30,34,35]. Another algorithm was published by Garrett Jr. et al [6]. In this instance, operative or interventional treatment is again suggested for symptomatic patients and the procedure should depend on the morphology and location of the dissection.…”
Section: Discussionmentioning
confidence: 99%
“…The successive course of the dissection starts with progressive thrombosis of the false lumen and continues with progressive dissection to distal branches, finally resulting in either rupture through the adventitia or the expansion of the false lumen [4,5]. A review of the literature recently reported that about 88% of all cases published to date concern men at an mean age of 54 years [6]. As abdominal pain is the most frequent sign of symptomatic IDSMA, it has been classified into grade I (peritonitis absent) and grade II (peritonitis present) [7].…”
Section: Introductionmentioning
confidence: 99%